Effect ofMeasurement Method and Wet Sieving Time on Index of Soil Aggregate Stability - Dwi Putro Tejo Baskoro; Henry D. Manurung (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
Aggregate stability is one of the important factors to be taken into account in controlling soil degradation. It influences soil ability to resist soil erosion. Therefore, it is necessary to have accurate measurement of aggregate stability that able to express well its resistance to dispersion. In this study, aggregate stability of various soil types were measured using different wet sieving time and aggregate size. Latosol Sindangbarang showed the highest aggregate stability index (ASI), followed by Podsolik Jasinga, Andosol Sukamantri, Lalosol Darmaga, and Regosol Sindangbarang Wei sieving time significantly affected AS!. The ASI decreased as wet sieving time increased The result also showed that different methods result in significantly different stability index. The method that used smaller size aggregates (< 2.83 mm) results in about 3 to 4 times higher stability index.